Ernest Bevin - BBC radio broadcast 1940 (United Kingdom, 1940)
1940 1939-1945 "Ernest Bevin - BBC radio broadcast 1940" [HFR0040], 1940 Ernest Bevin, Minister for Labour and National Service, gave regular broadcasts on the British Broadcasting Corporation Home and Overseas Services between 1940 and 1945. A series of specific talks on the role of the trade union movement was entitled 'The Voice of Labour'.